Factors Related to the Incidence of Hypertension in the Elderly - Firman Prastiwi; Amin Aji Budiman; Nikma Alfi Rosida (Universitas Aisyah Pringsewu, 2023)
The elderly will experience many physical and mental changes that can affect the incidence of hypertension. However, the results of several studies were different regarding what factors can affect elderly hypertension, so this can be used as a reference for further research. This study aims to determine what factors can influence the incidence of hypertension in the elderly at Panti Jompo Sabar Hati Banyuanyar. This study used a cross-sectional design with a sample of 84 elderly people at the Panti Jompo Sabar Hati Banyuanyar, Indonesia. The samples were collected using a total sampling technique. The tools used in this study were characteristic distribution instruments consisting of age, gender, family history, and lifestyle questionnaires consisting of histories of smoking and physical activity. The data analysis used was the chi-square test and multiple logistic regression tests. The results of the Chi Square test showed that there was no relationship between physical activity (p 0.418 and OR 1.600) and age (p 0.772 and OR 1.292) with the incidence of hypertension in the elderly. The results of the Chi Square test also showed that there was a significant relationship between gender (p 0.028 and OR 0.309), family history of hypertension (p 0.018 and OR 3.316), and history of smoking (p 0.045 and OR 3.061) with the incidence of elderly hypertension. In conclusion, there is a relationship between gender, family history, and smoking history with the incidence of hypertension in the elderly. However, there is no relationship between age and physical activity with the incidence of hypertension in the elderly. Abstrak: Lansia akan banyak mengalami berbagai perubahan pada fisik dan mental yang dapat berpengaruh terhadap kejadian hipertensi. Namun, hasil beberapa penelitian didapatkan berbeda terkait faktor apa saja yang dapat mempengaruhi hipertensi lansia sehingga hal ini dapat dijadikan acuan untuk penelitian lebih lanjut. Penelitian ini bertujuan untuk mengetahui factor apa saja yang dapat mempengaruhi kejadian hipertensi pada lansia di Panti Jompo Sabar Hati Banyuanyar. Penelitian ini menggunakan studi potong lintang dengan jumlah sampel 84 lansia di Panti Jompo Sabar Hati Banyuanyar, Indonesia. Sampel diambil dengan pendekatan teknik total sampling. Alat yang digunakan pada penelitian yaitu instrumen distribusi karakteristik terdiri dari usia,jenis kelamin, riwayat keluarga dan kuisioner gaya hidup yang terdiri dari riwayat merokok dan aktivitas fisik. Analisis data yang digunakan menggunakan uji chi-square dan uji regresi logistik berganda. Hasil uji Chi Square diperoleh tidak terdapat hubungan aktivitas fisik (p 0,418 dan OR 1,600) dan usia (p 0,772 dan OR 1,292) dengan kejadian hipertensi pada lansia. Hasil uji Chi Square juga menunjukan terdapat hubungan yang signifikan jenis kelamin (p 0,028 dan OR 0,309), riwayat keluarga hipertensi (p 0,018 dan OR 3,316), dan riwayat merokok (p 0,045 dan OR 3,061) dengan kejadian hipertensi lansia. Kesimpulannya terdapat hubungan jenis kelamin, riwayat keluaga dan riwayat merokok pada kejadian hipertensi lansia. Namun, tidak terdapat hubungan usia dan aktivitas fisik dengan kejadian hipertensi lansia.